Stepping Closer: Strategies to Attract Influencers in the Shopee Affiliate Program on Instagram - Harsono, Moh; Qomariah, Nurul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Content analysis was carried out by examining the Instagram posts of influencers involved in the Shopee affiliate program. This activity is to evaluate content style, post types, posting frequency, interaction with followers, and how influencers promote Shopee products. This analysis helps in understanding how influencers utilize the Instagram platform as a marketing channel. Thematic analysis was conducted by identifying common themes that emerged from interviews and content analysis. Researchers also looked for patterns in the content marketing strategies used by influencers, including a focus on creativity, interaction with followers, use of Instagram features, and the impact of the Shopee affiliate program on their content. During the analysis process, researchers looked for connections between findings from interviews, content analysis and official Shopee data. This helps researchers to identify general patterns and important findings that can help answer research questions. By combining this qualitative approach, researchers hope to provide an in-depth understanding of the content marketing strategies used by influencers through the Shopee affiliate program on Instagram. It is hoped that the results of this research will provide valuable insights for companies, marketers and researchers who are interested in the context of influencer marketing and e-commerce in Indonesia.